Working memory filtering at encoding and maintenance in healthy ageing, Alzheimer’s and Parkinson’s disease - Sofia Toniolo; Robert Udale; Verena Svenja Klar; Maria Raquel Maio; Bahaaeddin Attaallah; George K Tofaris; Michele T Hu; Sanjay G Manohar; Masud Husain (Scientific Reports)
Abstract The differential impact on working memory (WM) performance of distractors presented at encoding or during maintenance was investigated in Alzheimer’s Disease (AD), Parkinson’s Disease (PD) patients, elderly (EHC) and young healthy controls (YHC), (n = 28 per group). Participants reported the orientation of an arrow from a set of either two or three items, with a distractor present either at encoding or at maintenance. MRI data with hippocampal volumes was also acquired. Mean absolute error and mixture model metrics i.e., memory precision, target detection, misbinding (swapping the features of an object with another probed item) and guessing were computed. EHC and PD patients showed good filtering abilities both at encoding and maintenance. However, AD patients exhibited significant filtering deficits specifically when the distractor appeared during maintenance. In healthy ageing there was a prominent decline in WM memory precision, whilst in AD lower target detection and higher guessing were the main sources of error. Conversely, PD was associated only with higher guessing rates. Hippocampal volume was significantly correlated with filtering during maintenance – but not at encoding. These findings demonstrate how healthy ageing and neurodegenerative diseases exhibit distinct patterns of WM impairment, including when filtering irrelevant material either at encoding and maintenance.